The Implementation of POE (Predict, Observe, Explain) Learning Model to Improve Students’ Achievement at Class XI Students of SMA Negeri 10 Makassar - Sukma Marzuki; Bellona Mardhatillah Sabillah (Hasanuddin University, 2020)
This study aimed to determine the implementation of POE (predict, observe, explain) learning model to improve students’ achievement at class XI students of SMA Negeri 10 Makassar. This type of research was classroom action research consisting of two cycles. Each cycle of classroom action research was carried out in four (4) stages, namely: planning, implementing,observing, and reflecting. The subjects in this study were 35 class XI students in SMA Negeri 10 Makassar. The result of research indicated that there were 6 students (68.85%) in cycle I and 33 students (94.28%) in cycle II that achieved minimum completeness criteria. This research can be concluded that POE learning model can develop students ideas by relating experiences or stories that have been obtained previously. Besides, students' creativity in using diction is very good when presenting the prediction results using the POE method. Thus it is necessary to develop a learning model in the teaching and learning process so that students know very well the meaning of the assessment process of various learning activities.